Pengaruh Overconfidence, Loss Aversion, FOMO, dan Behavioral Herding terhadap Keputusan Investasi Saham pada Masa Volatilitas Tinggi - Geri Mahesa; Terrylina Arvinta Monoarfa; Sefrimel Angriani ZN (Indo Publishing, 2026)
This study aims to examine the influence of overconfidence, loss aversion, fear of missing out (FOMO), and behavioral herding on stock investment decisions during periods of high market volatility among retail investors in Jakarta. This study employed a quantitative research approach using a survey method. The population consisted of retail investors domiciled in Jakarta, with a sample of 384 respondents selected through a non-probability sampling technique. Data were collected using a structured questionnaire with a Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that overconfidence has a positive and significant effect on stock investment decisions during periods of high market volatility (t = 3.124 > 1.96; p = 0.003; β = 0.290). Loss aversion has a negative but insignificant effect (t = 0.904 < 1.96; p = 0.350; β = −0.079). Furthermore, fear of missing out (FOMO) has a positive and significant effect (t = 1.989 > 1.96; p = 0.029; β = 0.205), while behavioral herding also has a positive and significant effect (t = 2.113 > 1.96; p = 0.035; β = 0.278). The results suggest that psychological factors, particularly overconfidence, FOMO, and behavioral herding, play an important role in influencing stock investment decisions during periods of high market volatility, whereas loss aversion has not been proven to significantly affect investment decisions. These findings are expected to provide valuable insights for investors in understanding the influence of behavioral biases on investment decision-making under volatile market conditions..